PESQUISA E DESENVOLVIMENTO DE MELHORIAS EM UMA MÁQUINA PARA COLHEITA DE PLANTAS AROMÁTICAS - Kersting, Filipe; Pereira, Jean C. B.; Borges, Pablo O.; Sost, Jeferson d. B.; Valdiero, Antonio C. (Salão do Conhecimento, 2013)
Resumo